The Phylogeny of Parasitic Hemiptera Using Multivariate Statistical Package Cluster Analysis - Astuti, Dwi Setyo; Nugroho, Murwanto Setyo (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Hemiptera is an Insecta with the characteristic of the forewing which has been modified as a "hemelitron", namely half of the part at the base is thickened, while the rest is structured like a membrane, and the hind wing is like a thin membrane. Most of Hemiptera are parasite that attack rice plants. The purpose of this study was to determine the kinship of Hemiptera parasite species in rice fields in the Tulung area, Klaten , Central Java. The data obtained in this study is the identification of Hemiptera based on 30 morphological characters. Data analysis carried out using cluster analysis with MVSP (Multivariate Statistical Package) software. The results showed that there were 9 species of Hemiptera as parasitic species namely Gerris lacusticus, Narvesus carolinensis, Dysdercus cingulatus, Leptoglossus clypealis, Triatoma sanguisuga, Arilus cristatus, Thyanta custator, Padops cinctipes and Boisea trivittata. The most closely related species is Narvesus carolinensis and Arilus cristatus, yes, with a similarity rate of 86.9%. While the species that have the most distant kinship are Narvesus carolinensis and Gerris lacusticus that is equal to 60.4%. The high degree of similarity indicates a close relationship between parasite species.